Autonomous roles for the cytoplasmic domains of the CD2 and CD4 T cell surface antigens. - Beyers, A; Davis, S; Cantrell, D; Izquierdo, M; Williams, A (1991)
CD2 and CD4 are single chain transmembrane T cell surface molecules that are involved in signal transduction. Chimaeric constructs from rat CD2 and CD4 antigens were expressed in the Jurkat human T cell line to examine the role of extracellular, transmembrane and cytoplasmic domains in mediating functions controlled by CD2 and CD4. The results show that the large rise in concentration of cytoplasmic free Ca2+ mediated via CD2 crosslinking is controlled by the cytoplasmic domain and does not require the CD2 transmembrane and extracellular domains. Similarly the CD4 cytoplasmic domain alone was shown to encode the specificity for binding to the p56lck tyrosine kinase and to control down-modulation of CD4 after treatment with phorbol ester. Evidence was obtained that down-modulation of CD4 occurs when p56lck dissociates from the cytoplasmic domain due to phosphorylation of Ser 405.